Triple procedure for coexistent aphakia, squint, and iris defect: single-stage strabismus correction, glued IOL, and single-pass 4-throw pupilloplasty. Issue 12 (December 2020) - Agarwal, Rinky; Yadav, Neha; Tiwari, Kabita; Bafna, Rahul Kumar
Abstract : Posttraumatic aphakia is a serious deterrent to visual rehabilitation that usually follows sensory exotropia, thereby mandating urgent surgical intervention. In addition, abnormal iris configuration and iris defects postocular trauma can lead to amblyopia and glare and require surgical correction. However, in individuals where such multiple posttraumatic extraocular and intraocular abnormalities coexist, confusion remains about whether to perform sequential or concomitant surgeries. In these situations, an unusual triple technique consisting of strabismus correction, glued scleral fixation of intraocular lens, and single-pass 4-throw pupilloplasty is a useful cost-effective method of single-stage visual and cosmetic rehabilitation. However, it requires collaboration of experienced surgeons form multiple ophthalmic subspecialties.